Pengaruh Citra Merek Dan Kepercayaan Merek Terhadap Loyalitas Merek Pada Produk Yamaha (Studi Kasus Pada Mahasiswa/I Universitas Muhammadiyah Sumatera Utara - Rini Astuti; Aldi Alfarizky (CERED Indonesia Institute, 2020)
The purpose of this study was to determine and analyze the effect of brand image on brand loyalty, to know and analyze the effect of brand trust on brand loyalty and to know and analyze the influence of brand image and brand trust on brand loyalty on Yamaha products (Case studies on university students Muhammadiyah North Sumatra). The approach used in this research is an associative approach. The population in this study were all students of the University of Muhammadiyah North Sumatra. While the samples that met the criteria for sampling the observations made were 100 respondents. Data collection techniques in this study used a questionnaire technique. Data analysis techniques in this study used the Classic Assumption Test, Multiple Regression, Hypothesis Test (t Test and F Test), and the Coefficient of Determination. Data processing in this study uses the SPSS (Statistic Package for the Social Sciens) software program version 24.00. Partially known that brand image has a positive and significant influence on brand loyalty in Yamaha products. Partially known that brand trust has a positive and significant influence on brand loyalty on Yamaha products. Simultaneously it is known that brand image and brand trust have a significant effect on brand loyalty on Yamaha products